2015
DOI: 10.1111/ajt.13399
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Stimulation History Impacts Donor-Specific CD8+ T Cell Susceptibility to Costimulation/Integrin Blockade Based Therapy

Abstract: Recent studies have shown that the quantity of donor-reactive memory T cells is an important factor in determining the relative heterologous immunity barrier posed during transplantation. Here, we hypothesized that the quality of T cell memory also potently influences the response to costimulation blockade-based immunosuppression. Using a murine skin graft model of CD8+ memory T cell-mediated costimulation blockade resistance, we elicited donor-reactive memory T cells using three distinct types of pathogen inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 56 publications
1
30
1
Order By: Relevance
“…First, these data demonstrate differences in the quantity and quality of donor-reactive memory CD8 + T cells elicited via distinct types of exposure and highlight the fact, as we previously reported (31), that the heterogeneity of alloreactive CD8 + T cell memory might necessitate tailored therapeutic targeting for optimal control. We previously showed that antagonism of either LFA-1 or VLA-4 synergized with a regimen consisting of CTLA-4 Ig and anti-CD154 to prolong survival in animals possessing donor-specific CD8 + memory T cells elicited via the Listeria-OVA system used here (54).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…First, these data demonstrate differences in the quantity and quality of donor-reactive memory CD8 + T cells elicited via distinct types of exposure and highlight the fact, as we previously reported (31), that the heterogeneity of alloreactive CD8 + T cell memory might necessitate tailored therapeutic targeting for optimal control. We previously showed that antagonism of either LFA-1 or VLA-4 synergized with a regimen consisting of CTLA-4 Ig and anti-CD154 to prolong survival in animals possessing donor-specific CD8 + memory T cells elicited via the Listeria-OVA system used here (54).…”
Section: Discussionsupporting
confidence: 55%
“…As we have previously published, antigen-specific T cell responses peaked at day 10 and formed a detectable population of memory CD8 + T cells by day 30 (ref. 31 and data not shown). Skin graft rejection in this model is dependent on donor-reactive Thy1.1 + memory CD8 + T cells because administration of an anti-Thy1.1-depleting antibody eliminated the rejection response (31).…”
Section: Cd8mentioning
confidence: 76%
See 2 more Smart Citations
“…While some studies suggest that memory T cells do not require costimulation for reactivation, others have reported that costimulation remains necessary for their recall activation and expansion in vivo (40)(41)(42)(43)(44)(45). By carefully tracking endogenous donor-specific T cells using the IFN-γ ELISPOT assay as well as with fluorescently labeled 2W:I-A b and OVA:K b multimers, we observed that CTLA4-Ig was able to prevent the expansion of donor-specific T cells in sensitized mice.…”
Section: Cd4mentioning
confidence: 99%